Effects of Progressive Muscle Relaxation with Music and Aromatherapy on Decreasing Stress Levels among Teachers - Dewi, Claudia Fariday; Margawati, Ani; Mu’in, Muhammad (Department of Nursing, Faculty of Medicine, Diponegoro University, 2018)
Background: Stress among teachers has a significant relationship with the psychosomatic and depressive symptoms. Progressive muscle relaxation with music and aromatherapy is an intervention which can be implemented to reduce the level of stress among teachers.Purpose: This study aimed to investigate the effects of progressive muscle relaxation with music and aromatherapy on decreasing the level of stress among teachers.Methods: This study employed a pre-posttest quasi-experimental design with a control group. The samples were 46 teachers recruited by purposive sampling and were evenly assigned to the intervention group and the control group. Progressive muscle relaxation with music and aromatherapy was given to the intervention group for four sessions in four days; each lasted for 20 minutes. The data were collected using the Teacher Stress Inventory and analyzed using the t-test to know the effects of the intervention.Results: The results showed that the mean of stress level among the teachers in the intervention group decreased from 50.65±3.761 to 32.78±8.426 after the intervention. Meanwhile, in the control group, the mean of stress level slightly decreased from 49.87±3.348 to 49.17±4.868. The t-test obtained a p-value of 0.000, indicating that there were significant differences in the stress levels between the intervention and the control group.Conclusion: Progressive muscle relaxation with music and aromatherapy reduced the level of stress among teachers. Based on the findings, it is recommended that community nurses promote this relaxation therapy to decrease the stress level among school teachers.